2008
DOI: 10.1016/j.ijresmar.2008.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Licensing exchange—Insights from the biopharmaceutical industry

Abstract: a b s t r a c t a r t i c l e i n f o Article history: First received in 16 August 2007 and was under review for 5 and a half months Area Editor: Aric RindfleischLicensing out technologies is a main source of revenue for dedicated technology firms. While licensing exchange has received very little attention in prior marketing literature, it is economically important and poses particular challenges. One major obstacle for obtaining new licensing deals is the information asymmetry between licensors and licensees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…On the contrary, as expected, biopharmaceutical firms' RPD enhances firm performance, but excessive RPD hampers it. This result aligns with the existing findings on RPD and performance, which suggest a balanced RPD (Filiou & Massini, 2018;Leten et al, 2007;Wuyts & Dutta, 2008). Owing to high product development complexity, developing a new product that is related to a firm's existing offering is a better choice regarding risk management and efficiency enhancement.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…On the contrary, as expected, biopharmaceutical firms' RPD enhances firm performance, but excessive RPD hampers it. This result aligns with the existing findings on RPD and performance, which suggest a balanced RPD (Filiou & Massini, 2018;Leten et al, 2007;Wuyts & Dutta, 2008). Owing to high product development complexity, developing a new product that is related to a firm's existing offering is a better choice regarding risk management and efficiency enhancement.…”
Section: Discussionsupporting
confidence: 88%
“…In the biopharmaceutical industry, Wuyts and Dutta (2008) found that an effect on new licensing deals in biotechnology firms eventually assumes an inverted U-shape, even if they move to central positions in the licensing exchange network where the firms can obtain new license deals. When the firms disclose strategic information, more new license agreements can be obtained; however, too much information disclosure could reveal the dark side of network centrality.…”
Section: Different Product Development Strategies Between the Pharmac...mentioning
confidence: 99%
“…Such frictions are typically related to the lack of relevant information about the quality of idea sellers and/or of their ideas. For instance, prior work has pointed out the existence of relevant information asymmetries between sellers and buyers about the value of ideas—whose real quality might be better known by inventors than by potential buyers—such that markets for technologies might be afflicted by a “lemons” problem, which reduces the volume of technology transactions (Aghion & Tirole, 1994; Akerlof, 1970; Anton & Yao, 2002; Gallini & Wright, 1990; Pisano, 2006; Wuyts & Dutta, 2008). Other prior research points to contexts in which neither buyers nor sellers know exactly whether a certain idea can be successfully commercialized (Agrawal et al, 2015; Arora & Gambardella, 2010a).…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…Several scholars have outlined how uncertainty and lack of information could represent key obstacles to the smooth functioning of markets for technology (Agrawal et al, 2015; Ceccagnoli et al, 2014; Fosfuri & Giarratana, 2010; Gans et al, 2008; Luo, 2014). Previous research points out the existence of situations where there are relevant information asymmetries between sellers and buyers about the value of ideas—whose real quality might be better known by inventors than by potential buyers (Aghion & Tirole, 1994; Akerlof, 1970; Anton & Yao, 2002; Gallini & Wright, 1990; Pisano, 2006; Wuyts & Dutta, 2008)—or in which neither buyers nor sellers know exactly whether a certain idea can be successfully commercialized (Agrawal et al, 2015; Arora & Gambardella, 2010a). Nearly all of this prior work suggests that more information—especially more information about external collaborators and ideas—will be good for any agent transacting in the market and for overall social welfare as more and higher‐quality innovations will be eventually commercialized (Agrawal et al, 2015; Arora et al, 2001; Hegde & Luo, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The economic, finance and strategic management literature has often identified the information asymmetry that can lead to a Lemons Problem as an important element of transactions involving licensing and technology transfer in high technology industries (Gallini and Wright, 1990; Wuyts and Dutta, 2008), including the biotech industry (Lerner and Merges, 1998; Antelo, 2003; Audretsch and Feldman, 2003; Rothaermel and Deeds, 2004; Pisano, 2006, unpublished manuscript; Mason et al, 2008). The central hypothesis has been that the company originating the product has superior information compared to the in-licensor, and as such it would only seek to out-license drugs of inferior quality while keeping the good ones for internal development.…”
Section: Introductionmentioning
confidence: 99%